From proteome to candidate vaccines: target discovery and molecular dynamics-guided multi-epitope vaccine engineering against kissing bug - Albaqami, Faisal F.; Altharawi, Ali; Althurwi, Hassan N.; Alharthy, Khalid M. (Frontiers in Immunology, 2024)
Trypanosoma cruzi is a protozoan parasite that causes the tropical ailment known as Chagas disease, which has its origins in South America. Globally, it has a major impact on health and is transported by insect vector that serves as a parasite. Given the scarcity of vaccines and the limited treatment choices, we conducted a comprehensive investigation of core proteomics to explore a potential reverse vaccine candidate with high antigenicity. To identify the immunodominant epitopes, T. cruzi core proteomics was initially explored. Consequently, the vaccine sequence was engineered to possess characteristics of non-allergenicity, antigenicity, immunogenicity, and enhanced solubility. After modeling the tertiary structure of the human TLR4 receptor, the binding affinities were assessed employing molecular docking and molecular dynamics simulations (MDS). Docking of the final vaccine design with TLR4 receptors revealed substantial hydrogen bond interactions. A server-based methodology for immunological simulation was developed to forecast the effectiveness against antibodies (IgM + IgG) and interferons (IFN-g). The MDS analysis revealed notable levels of structural compactness and binding stability with average RMSD of 5.03 Å, beta-factor 1.09e+5 Å, Rg is 44.7 Å and RMSF of 49.50 Å. This is followed by binding free energies calculation. Proteins usually exhibit a combination of flexibility and stiffness, particularly about the residues located in close proximity to the binding site. The system stability was compromised by the complexes, as evidenced by their corresponding Gibbs free energies of -54.6337 kcal/mol. These results will be very helpful to vaccine scientists in creating a very successful vaccination and a viable therapeutic approach for Chagas disease.